Two national surveys of American Jews, 2000-01: A comparison of the NJPS and AJIS - Joel Perlmann (Levy Economics Institute of Bard College, 2007)
While there have been very few national surveys of American Jews, two that we do have are from the same period, 200001. They were conducted by different researchers using different sampling methods. Known as the NJPS and the AJIS, these surveys are now available as public-use datasets, but they have not yet been systematically compared. This paper first describes what modifications in sample composition must be made to meaningfully compare the surveys' results. Then it reviews basic demographic and cultural orientations of respondents; on most measures, the samples are quite similar. The paper stresses that both surveys can be thought of as samples of Americans of recent Jewish origin; and in both surveys, a large minority of people have both Jewish and non-Jewish origins (typically as the products of parental intermarriage). Many of these respondents do not report themselves Jewish by religion; indeed, many declare that they are Christians. One notable feature of the surveys is that the AJIS sample includes modestly more people of Jewish origin who do not identify themselves as Jewish by religion today. The paper concludes by urging the importance of asking all respondents who did not declare themselves Jewish by religion the question, Do you consider yourself Jewish in any way?
Keywords: 330